2016
DOI: 10.18632/oncotarget.10778
|View full text |Cite
|
Sign up to set email alerts
|

Genomic complexity and dynamics of clonal evolution in childhood acute myeloid leukemia studied with whole-exome sequencing

Abstract: Despite significant improvement in treatment of childhood acute myeloid leukemia (AML), 30% of patients experience disease recurrence, which is still the major cause of treatment failure and death in these patients. To investigate molecular mechanisms underlying relapse, we performed whole-exome sequencing of diagnosis-relapse pairs and matched remission samples from 4 pediatric AML patients without recurrent cytogenetic alterations. Candidate driver mutations were selected for targeted deep sequencing at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 55 publications
1
45
0
Order By: Relevance
“…6 Other studies have reported a high frequency (;20%) of SETD2 alterations in chemotherapy-resistant, MLL-arranged ALL and AML and hepatosplenic T-cell lymphoma. 9 A lower frequency of SETD2 alterations are found in other hematological malignancies, including early T-cell precursor ALL, 10 non-MLL-rearranged AML, 11 and chronic lymphocytic leukemia (CLL) 12 ( Figure 1A; supplemental Table 1, available on the Blood Web site) and multiple solid tumors. [13][14][15][16][17] SETD2 loss has been associated with adverse clinical outcomes in clear cell renal cell carcinoma, 18,19 and CLL 12 and has been shown to accelerate disease and increase cell proliferation in some experimental models.…”
Section: Introductionmentioning
confidence: 99%
“…6 Other studies have reported a high frequency (;20%) of SETD2 alterations in chemotherapy-resistant, MLL-arranged ALL and AML and hepatosplenic T-cell lymphoma. 9 A lower frequency of SETD2 alterations are found in other hematological malignancies, including early T-cell precursor ALL, 10 non-MLL-rearranged AML, 11 and chronic lymphocytic leukemia (CLL) 12 ( Figure 1A; supplemental Table 1, available on the Blood Web site) and multiple solid tumors. [13][14][15][16][17] SETD2 loss has been associated with adverse clinical outcomes in clear cell renal cell carcinoma, 18,19 and CLL 12 and has been shown to accelerate disease and increase cell proliferation in some experimental models.…”
Section: Introductionmentioning
confidence: 99%
“…ASXL3 mutations are present in a variety of malignancies, including 10% of melanomas and lung adenocarcinoma, but its role in hematologic malignancies is unclear 2,11 . ASXL3 is expressed in the bone marrow 11 but ASXL3 mutations are rare in myeloid neoplasms: one patient with an ASXL3 mutation was identified in the AML TCGA study 12 and one case of pediatric AML with a point mutation clone that significantly expanded from less than 1% at initial diagnosis to 30% at relapse has also been identified 13 . Unlike ASXL1/2, ASXL3 mutations are rare in AML with t (8;21), where a single case was identified in a cohort of 110 cases 14 .…”
Section: Editorialmentioning
confidence: 99%
“…Recent high-throughput genome wide sequencing has shed light on the role of somatic mutations, including signal transduction molecules involved in AML [5]. These mutations generally involve protein tyrosine kinases (PTKs) that confer upon these cells a proliferative advantage.…”
Section: Introductionmentioning
confidence: 99%